THE ARCHITECTURE OF NATIONAL AWAKENING: JADIDISM AND THE TRANSFORMATION OF TURKIC LITERARY AND SOCIO-POLITICAL THOUGHT - Eshboyeva , Madina; Eshboyev , Temur (Scientific practical conference, 2026)
This article explores the ideological and aesthetic foundations of the Jadid movement (Jadidism) and its profound influence on Turkic literature during the late 19th and early 20th centuries. Drawing from materials presented at the international scientific conference "The Jadid Movement and the Problem of Studying Its Influence on the Literature of Turkic Peoples" (Karshi, 2023), it examines the movement's socio-political goals, its literary innovations, and its role in shaping national identity. The analysis highlights how Jadid thinkers integrated traditional Turkic-Islamic heritage with modern Western educational and administrative models to pursue national liberation and cultural enlightenment.